SITE PRODUCTIVE CAPACITY OF TECTONA GRANDIS YOUNG STANDS IN TWO REGIONS OF MATO GROSSO STATE – BRAZIL - DRESCHER, Ronaldo; NUNES, Gustavo Manzon; MARTINEZ, Diego Tyszka; PELISSARI, Allan Libanio (Brazilian Journal of Biometrics, 2016)
Considering the increasing necessity for detailed information to guide the management of Tectona grandis homogeneous stands, this study aimed to determine and to evaluate the site productive capacity in young stands of two regions of Mato Grosso State, Brazil. Thus, we used data of homogeneous stands of up to 11 years old in the municipalities of Santo Antonio do Leverger and Brasnorte. Therefore, the equation generated by monomolecular model describes in an appropriate and an efficient form the dominant height behavior to determine the site productive capacity, whose Tectona grandis development was higher in Mato Grosso State, when it compared with Africa and Asia regions, and it is similar to Central and South America sites. This demonstrates the importance of this forest culture to supply the forest sector and to attend the international demands of noble feedstock as well as to reduce human pressure on the natural forests.